Concomitant Exposure to Ovalbumin and Endotoxin Augments Airway Inflammation but Not Airway Hyperresponsiveness in a Murine Model of Asthma - Mac Sharry, John (Public Library of Science, 2014)
Varying concentrations of lipopolysaccharide (LPS) in ovalbumin (OVA) may influence the airway response to allergic sensitization and challenge. We assessed the contribution of LPS to allergic airway inflammatory responses following challenge with LPS-rich and LPS-free commercial OVA. BALB/c mice were sensitized with LPS-rich OVA and alum and then underwent challenge with the same OVA (10 µg intranasally) or an LPS-free OVA. Following challenge, bronchoalveolar lavage (BAL), airway responsiveness to methacholine and the lung regulatory T cell population (Treg) were assessed. Both OVA preparations induced BAL eosinophilia but LPS-rich OVA also evoked BAL neutrophilia. LPS-free OVA increased interleukin (IL)-2, IL-4 and IL-5 whereas LPS-rich OVA additionally increased IL-1β, IL-12, IFN-γ, TNF-α and KC. Both OVA-challenged groups developed airway hyperresponsiveness. TLR4-deficient mice challenged with either OVA preparation showed eosinophilia but not neutrophilia and had increased IL-5. Only LPS-rich OVA challenged mice had increased lung Tregs and LPS-rich OVA also induced in vitro Treg differentiation. LPS-rich OVA also induced a Th1 cytokine response in human peripheral blood mononuclear cells.We conclude that LPS-rich OVA evokes mixed Th1, Th2 and innate immune responses through the TLR-4 pathway, whereas LPS-free OVA evokes only a Th2 response. Contaminating LPS is not required for induction of airway hyperresponsiveness but amplifies the Th2 inflammatory response and is a critical mediator of the neutrophil, Th1 and T regulatory cell responses to OVA.